Perception of Construction Industry Players on Carbon Dioxide Reduction through Planning and Design Stage in Project Life Cycle - Tan, Shu Qi; Seow, Ta Wee; Goh, Kai Chen; Shafii, Haryati (Research in Management of Technology and Business, 2023)
The construction industry played a considerable role in rising carbon dioxide emissions. Construction industry players did not properly handle the project life cycle, which brings in carbon dioxide emissions that indirectly contributes to global warming and climate change. So, the carbon dioxide emission become more challenging due to construction’s planning and design stage in project life cycle. The objectives of the research are to identify the perception of construction industry on carbon dioxide reduction through planning and design stage in project life cycle and to purpose carbon dioxide reduction strategies through planning and design stage in project life cycle. The research has been implemented by quantitative method which a questionnaire survey was distributed to construction players like architect, engineer, quantity surveyor and project manager from the state of Johor Bahru and the survey was obtained from 55 respondents. Statistical Package for Social Science (SPSS) were analyzed the data collected. The findings guide efforts to reduce the carbon dioxide emissions in construction industry by assisting construction key players in providing a better strategy through planning and design stage in project life cycle. Construction industries strive towards to solve the problem of carbon dioxide emissions to decrease environmental impacts and become environmentally friendly. In conclusion, the study is completed successfully as all objectives are achieved.